Sześcioksiąg w mozaikach bazyliki Santa Maria Maggiore w Rzymie - Adamiak, Stanisław (Biblica et Patristica Thoruniensia, 2011)
The main nave of the Santa Maria Maggiore at Rome has been decorated with 42 mosaic panels, presenting the scenes from the Pentateuch and the Book of Josue. The mosaics were created at the time of the construction of the basilica in the first half of the fifth century and thus they are the oldest monumental Bible illustration cycle. Some illuminated codices probably served as a model for the mosaics, but the final result is rather an original conception, linked theologically with the mosaics of the triumphal arch of the basilica. The paper describes the surviving 27 mosaics. Their conformance to traditional Roman iconography is underlined. The main idea behind the cycle is interpreted as an attempt to convince the people of Rome that the history of the People of God, which begins with the patriarchs of the Old Testament, is as glorious and ancient as the Roman one.